Maternal and Perinatal Outcomes in Pregnant Women with Cystic Fibrosis - Gilmar de Souza Osmundo Junior; Rodrigo Abensur Athanazio; Samia Zahi Rached; Rossana Pulcineli Vieira Francisco (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objectives To assess the perinatal and maternal outcomes of pregnant women with cystic fibrosis (CF) and severe lung impairment. Methods This was a series of cases aiming to review the maternal and fetal outcomes in cases of singleton pregnant women with a diagnosis of CF. We have included all of the cases of singleton pregnancy in patients with CF who were followed-up at the obstetrics department of the Medical School of the Universidade de São Paulo, between 2003 and 2016. The exclusion criteria were the unattainability of the medical records of the patient, and delivery at other institutions. A forced expiratory volume in 1 second < 50% was considered as severe lung impairment. We have also analyzed data regarding maternal hospitalization and respiratory exacerbations (REs). Results Pregnant women with CF and severe lung impairment did not present an association with spontaneous prematurity, fetal growth restriction or fetal demise. All of the cases involved multiple RE episodes requiring antibiotic therapy. The median (range) of events per patient was of 4 (2-4) events. Conclusion Cystic fibrosis patients with severe lung impairment may achieve successful term pregnancies. However, pregnancies of women with CF are frequently complicated by REs, and this population may require hospital admission during the course of the pregnancy. Cystic fibrosis patients should be followed by a specialized team with experience in treating respiratory diseases.